PENGARUH PENGAITAN NILAI KEIMANAN DAN KETAQWAAN DALAM PEMBELAJARAN KIMIA TERHADAP MOTIVASI BELAJAR, PRESTASI BELAJAR, DAN PERSEPSI SISWA - Wiwin Puspita Hadi (Universitas Negeri Malang, 2016)
Abstrak Pendidikan nasional berfungsi untuk mengembangkan kemampuan dan membentuk watak serta peradaban bangsa yang bermartabat dalam rangka mencerdaskan kehidupan bangsa, pendidikan juga bertujuan untuk mengembangkan potensi peserta didik agar menjadi manusia yang beriman dan bertaqwa kepada Tuhan Yang Maha Esa, berakhlak mulia, sehat, berilmu, cakap, kreatif, mandiri, dan menjadi warga negara yang demokratis serta bertanggung jawab. Sesuai dengan tujuan yang sudah ada seharusnya sistem pembelajaran di Indonesia mampu menciptakan manusia Indonesia seutuhnya Penelitian ini dilakukan untuk mengetahui pengaruh pengaitan nilai keimanan dan ketaqwaan pada pembelajaran kimia terhadap motivasi belajar, prestasi belajar serta persepsi siswa terhadap pembelajaran tersebut. Rancangan yang digunakan adalah eksperimental semu. Sampel penelitian adalah siswa kelas X MA An Nur Banyuates Sampang, dengan kelas kontrol dan kelas eksperimen masing-masing 40 siswa.. Prestasi belajar siswa diketahui dengan tes tertulis (post test) yang berbentuk multiple choice, terdiri dari 25 item. Uji coba instrumen tes diperoleh reliabilitas 0,80 dan validitas isi 78,6%. Motivasi belajar siswa diketahui dengan menggunakan angket, dan persepsi siswa terhadap pembelajaran diketahui menggunakan lembar observasi. Hasil penelitian menunjukkan bahwa: (1) Siswa yang mendapat pembelajaran kimia yang dikaitkan dengan nilai keimanan dan ketaqwaan motivasi belajarnya lebih tinggi dibandingkan dengan siswa yang mengalami pembelajaran kimia tanpa dikaitkan dengan nilai keimanan dan ketaqwaan; (2) Siswa yang mendapat pembelajaran kimia dengan nilai keimanan dan ketaqwaan prestasi belajarnya lebih tinggi dibandingkan dengan siswa yang mengalami pembelajaran tanpa nilai keimanan dan ketaqwaan; (3) Persepsi siswa terhadap pembelajaran kimia yang dikaitkan dengan nilai keimanan dan ketaqwaan lebih positif dibandingkan dengan siswa yang mengalami pembelajaran tanpa dikaitkan nilai keimanan dan ketaqwaan. Kata Kunci: Keimanan, Ketaqwaan, Prestasi Belajar, Motivasi, Persepsi Abstract The function of national education is to develop and to embody ability, character and civilization to improve national life in order to grow students’ potency to be qualified human being with good in faith, religion, knowledge, health, behavior, creativity and talent. Moreover they should be independent, democratic and responsible person in their environment. Based on these objectives, Indonesian learning system should be able to create high quality person with excellent in religion and knowledge. These conditions will be achieved if all of teaching at schools, especially chemistry teaching, can be used to develop students’ knowledge, faith and piety. The objectives of this research is to know the effect of connecting faith and piety values in chemistry teaching upon students’ motivation, learning achievement, and perception. This research used quasi-experiment design. Population of this research was students in 10th grade of An Nur Senior High School Banyuates Sampang. Research sample consist of two classes, i.e. experimental and control classes. Each class consists of 40 students. The experimental class is subjected to chemistry teaching for hydrocarbon and petroleum topics connected to faith and piety values, whereas the control class is subjected to the same topics but not connected to faith and piety values. Students’ achievement was measured using objective written test consists of 25 items with content validity of 78.6% and reliability, measured with KR 20’s formula of 0.80. Student’s motivation was identified using a questionnaire, whereas student’s perception was identified using an observation form. The result of this research are as follows: (1) students subjected to chemistry teaching for hydrocarbon and petroleum topics connected to faith and piety values have higher motivation than those who studied the same topics but not connected to faith and piety values; (2) students subjected to chemistry teaching for hydrocarbon and petroleum topics connected to faith and piety values have higher achievement than those who studied the same topics but not connected to faith and piety; and (3) students subjected to chemistry teaching for hydrocarbon and petroleum topics connected to faith and piety values have more positive perception about chemistry teaching than those who studied the same topics but not connected to faith and piety values. Based on these results it is suggested to connect chemistry teaching for other topics with faith and piety values. Keywords: Faith, piety, learning achievement, motivation, perception.